The role of unions in the Twenty-first century : a report for the Fondazione Rodolfo Debenedetti - Boeri, Tito; Brugiavini, Agar; Calmfors, Lars, 1948- (Oxford University Press, 2001)
Focusing on the role and functions of trade unions, this collection of essays by a team of international scholars looks to the future and explores their broader political and social remits and responsibilities.